3-Phenoxymethyl-6-phenyl-1,2,4-triazolo[3,4-b][1,3,4]thiadiazole - Shaaban K. Mohamed; Joel T. Mague; Mehmet Akkurt; Etify A. Bakhite; Mustafa R. Albayati (IUCrData, 2016)
In the title compound, C16H12N4OS, the bicyclic triazolothiadiazole core is approximately planar, with an r.m.s. deviation of 0.018 Å. The phenyl rings are inclined to its mean plane by 7.66 (7) and 71.79 (7)°. In the crystal, molecules are linked via a C—H...π interaction and a π–π interaction [intercentroid distance = 3.2942 (9) Å] involving inversion-related triazole rings. These interactions result in the formation of chains propagating along [10-1].